Analysis of monoral transport (Transport systems and technologies, 2019)
The article discusses monorail transport (MT) by analysis of existing monorail systems (MS). It is established that this type of transport has a wide scope and is able to efficiently improve the transport services for the urban population and industrial complexes. The history of MT is described, the total length of passenger monorail lines has been counted and the length ratio depending on the location of MC is shown in the graph. A definition, description of the general characteristics and advantages of MS usage is provided. MT is classified depending on the type of vehicle, method for arranging relative to guides and chassis design.
Keywords: monorail transport, system, guide rail, length, carriage, designing, electric motor, pneumatic tire, infrastructure, technology